2017
DOI: 10.5433/1679-0359.2017v38n4suplp2641
|View full text |Cite
|
Sign up to set email alerts
|

Dry residue of cassava as a supplementation in broiler feed with or without addition of carbohydrases

Abstract: The objective of this study was to evaluate the inclusion of dry residue of cassava (DRC) with or without supplementation of carbohydrases on performance, carcass yield, cuts and organs, blood parameters and meat quality of broiler chickens. Birds were distributed in a completely randomised design in a 2 x 5 factorial scheme, with or without addition of carbohydrases and five levels of DRC inclusion, resulting in 10 treatments with 5 replicates of 22 birds each. At 21 days of age, two birds of each treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…abdo (%) Os resultados da gordura abdominal contrastam aos obtidos por Ribeiro et al (2006), que verificaram redução no seu percentual com o aumento do farelo integral da mandioca (0, 15, 30 e 45%) na dieta de frango caipira aos 84 dias. Carrijo et al (2010) e Broch et al (2017), da mesma maneira, observaram redução na gordura abdominal de frangos caipira e frangos da linhagem coob 500, respectivamente, alimentados com coprodutos da mandioca.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…abdo (%) Os resultados da gordura abdominal contrastam aos obtidos por Ribeiro et al (2006), que verificaram redução no seu percentual com o aumento do farelo integral da mandioca (0, 15, 30 e 45%) na dieta de frango caipira aos 84 dias. Carrijo et al (2010) e Broch et al (2017), da mesma maneira, observaram redução na gordura abdominal de frangos caipira e frangos da linhagem coob 500, respectivamente, alimentados com coprodutos da mandioca.…”
Section: Methodsunclassified
“…Resultado semelhante foi verificado por Souza et al (2011), com modificações na coloração da carcaça e das peles do peito de aves caipiras, variando do amarelo vivo para o branco, à medida que os níveis de substituição do milho pelo resíduo da industrialização da mandioca vão sendo incrementados, similarmente, Broch et al (2017), observaram diminuição dos valores de b* (P <0,05) para frangos de corte alimentados com resíduo da fecularia quando comparado ao tratamento controle, diferindo dos observados por Amorim et al (2015), que não encontraram efeito sobre os valores de colorimétrica da carne do peito.…”
Section: Methodsunclassified
“…The addition of alternative fibrous feedstuffs in poultry diets can compromise animal performance due to antinutritional factors. DCR has high levels of non-starch polysaccharides that cannot be digested by birds, because their binding is resistant to hydrolysis in the gastrointestinal tract (Broch et al, 2017) making it difficult to use successfully in poultry diets (Morgan & Choct, 2016). Nevertheless, according to Duarte et al (2013), quails might be able to make better use of fibrous feedstuffs when compared to broilers due to the morphophysiological characteristics of their gastrointestinal tract, enabling quails to have a more efficient digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…Unused cassava residue usually rots, pollutes the environment and endangers the health of both human and animals [3]. Research has shown that cassava residue has 74.4% of nitrogen-free extract content, 3519 Kcal/kg crude energy [4] and it is rich in amino acids and minerals such as copper, potassium, manganese and iron [5]. In addition, cassava residue is much cheaper compared with common feedstuffs like crushed maize, so that it is an unconventional feedstuff with great utility value for livestock.…”
Section: Introductionmentioning
confidence: 99%